1D modeling of SI engine using n-butanol as fuel: Adjust of fuel properties and comparison between measurements and simulation. (1st February 2018) - da Silva Trindade, Wagner Roberto; dos Santos, Rogério Gonçalves
Highlights: n-Butanol-gasoline blend called BU40 (40% n-butanol, 60% gasoline) was studied. A 1-D model of a SI engine has been calibrated and validated. BU40 fuel properties were estimated based on numerical-experimental calibration. Performance presented by BU40 is similar to E25, worse than E100, better than E0. Combustion pressure of BU40 is higher than E0 and E25, but lower than E100. Abstract: n-Butanol is an option of biofuel with potential to be used in the transportation industry. There is little information about performance of engines running with this alcohol and thus is very difficult to evaluate its advantages. A way to bypass this limitation is to use numerical simulation, mainly 1D models, to represent the whole engine and preview its performance running with different fuels. The lack of information about n-butanol and its combustion properties are big challenges to surpass when building these virtual models. A way to overcome these challenges is numerically model an engine and adjust the fuel properties until the numerical results are in agreement with test results. The aim of this work is to estimate fuel properties of an n-butanol-gasoline blend by means of numerical simulation, allowing the comparison of its performance against other fuels. Starting with a virtual engine model, the fuel properties were adjusted based on test measurements until a good agreement between numerical results and measured results was obtained. After numerical calibration, some of the main n-butanol fuel parameters (BU40) needed by 1D codes were obtained, like liquid fuel heat of vaporization @ 298 K = 583 kJ/kg, density = 813 kg/m 3, liquid fuel abs. entropy @ 298 K = 3015.78 J/kg-K, critical temperature = 563 K, critical pressure = 4.5 MPa, gaseous fuel abs. entropy @ 298 K = 4723.79 J/kg-K, among others. The properties thus obtained leaded to well approximated results, where numerical to experimental results for indicated mean effective pressure (IMEP) are lower than 0.1 bar, lower than 8% for peak cylinder pressure (PCP) and lower than 7% for rate of heat release (ROHR).